2015
DOI: 10.1038/srep10752
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of species-specific genes regulated by E2-2 in human plasmacytoid dendritic cells

Abstract: Dendritic cells (DCs) are sentinels of the immune system and comprise two distinct subsets: conventional DCs (cDCs) and plasmacytoid DCs (pDCs). Human pDCs are distinguished from mouse pDCs phenotypically and functionally. Basic helix-loop-helix protein E2-2 is defined as an essential transcription factor for mouse pDC development, cell fate maintenance and gene programe. It is unknown whether E2-2 regulation contributes to this species-specific difference. Here we investigated the function of E2-2 in human pD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 43 publications
(53 reference statements)
0
19
0
Order By: Relevance
“…5A and fig. S6A) (1819). In contrast, CD123 + CD11C −/lo AS DCs expressed cDC markers, including CD2 , CX3CR1 , CD33 /SIGLEC3, CD5 , and SIGLEC1 /CD169, both at protein and mRNA levels (Fig.…”
Section: Pdcs Are Phenotypically and Functionally Distinct From Cd123mentioning
confidence: 99%
“…5A and fig. S6A) (1819). In contrast, CD123 + CD11C −/lo AS DCs expressed cDC markers, including CD2 , CX3CR1 , CD33 /SIGLEC3, CD5 , and SIGLEC1 /CD169, both at protein and mRNA levels (Fig.…”
Section: Pdcs Are Phenotypically and Functionally Distinct From Cd123mentioning
confidence: 99%
“…In mice, inducible knockout of E2-2 gives rise to a cell that is markedly decreased in its ability to produce IFNs but more adapted to stimulate T cell responses [15]. This is recapitulated in human pDC cell lines where E2-2 knockdown decreases IFN production and increases the ability to induce T cell proliferation [15,17], though pDC leukemic cells lines produce little or no IFN and do not fully represent primary human pDC function [20][21][22][23]. It has also been demonstrated that mouse and human pDCs downregulate E2-2 in response to chronic viral infection [16,19].…”
Section: Discussionmentioning
confidence: 99%
“…STAT3, in turn promotes the expression of transcription factor E2-2 (TCF4) [11]. E2-2 is required for pDC development [10,11,15,16] and promotes canonical pDC phenotype and function [17].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations